Comparative study between trabeculectomy with photodynamic therapy (BCECF-AM) and trabeculectomy with antimetabolite (MMC) in the treatment of primary open angle glaucoma - Saeed AM (Dove Medical Press, 2012)
Ahmed M SaeedOphthalmology Department, Benha University, Benha, EgyptBackground: Various methods have been investigated to avoid postoperative scarring of the filtering bleb in modern glaucoma surgery. Most deal with the application of antimetabolic drugs such as mitomycin C (MMC). 2’,7’-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein, acetoxymethyl ester (BCECF-AM) is a locally acting intracellular photosensitizer which could control and decrease postoperative fibrosis at the trabeculectomy site.Purpose: To compare the effect of photodynamic therapy in combination with trabeculectomy to the effect of MMC combined with the same procedure in controlling postoperative intraocular pressure (IOP) in patients with medically uncontrolled primary open angle glaucoma (1ry OAG).Methods: A randomized controlled clinical trial was conducted on 76 eyes of 76 patients divided into three groups undergoing trabeculectomy, trabeculectomy with BCECF-AM (group A), trabeculectomy with MMC (group B), and trabeculectomy only as a control group (group C). Patients were reviewed postoperatively for clinical evaluation and photo documentation of the blebs with a fundus camera and ultrasonic biomicroscopy (UBM). The desirable effect of the adjunctive material was evaluated according to the clinical efficacy, tolerability, and safety by comparison with the control group.Setting: Benha University Hospital, Benha, Egypt.Results: After a mean follow-up of 24 months, all procedures succeeded in lowering IOP. The cumulative probability of complete success at the 24 month follow-up was 91% for group B, compared to 82% and 81.5% for group A and group C, respectively. The percentage of complete success was highest for group B, second highest for group A, and lowest for group C over the follow-up period; however, these differences were not statistically significant (P > 0.05). Regarding the bleb morphology and UBM reflectivity, the differences were not statistically significant (P > 0.05). The mean bleb height and breadth were larger in groups A and B in comparison to group C over the study period. The mean aqueous drainage route was similar in groups A and C, but less than in group B at 3 and 12 months postoperatively. Complications were generally mild and less marked in group A and C than group B.Conclusion: Cellular photoablation using BCECF-AM seems to be a feasible new method to use in combination with glaucoma filtration surgery. Although MMC might be considered a more potent adjunctive to trabeculectomy in promoting IOP reduction, photodynamic therapy carries relatively less risk of adverse effects and complications. Cellular photoablation using BCECF-AM could be considered efficient, tolerable and relatively safer in managing patients with 1ry OAG. Further studies are necessary to determine the safety and the reliability of this therapy.Keywords: photodynamic therapy, mitomycin C, trabeculectomy, open angle glaucoma, ultrasonic biomicroscopy